Questionnaire development: face validity and item impact testing of the Child Oral Health Impact Profile - Broder HL, McGrath C, Cisneros GJ (Blackwell Synergy, 2007)
The Child Oral Health Impact Profile (COHIP) was designed to assess oral-facial well-being in school-age children as reported by the child and via proxy report from a caregiver